ANALYSIS FACTOR OF LOCATION DECISION MAKING ON SME’S IN MANADO - Siagian, Shintya G.; Lapian, Joyece S.L.H.V.; Wangke, Shinta J.C. (Universitas Sam Ratulangi, 2020)
Abstract: The location decision making is an almost unavoidable thing for the failure and the success for a business. Every SME’s owner has different type of build their business, in the F and B industry the location is a place to serve the consumers, the accuracy of location selection is one of the factors that affecting the Business Success. In Manado SME’s in Fand B Industry has changed where there is online ordering is through an application in this era. This research analyzed the factors of location decision making In Manado. Analysis Method with 50 respondents and incidental sampling used to as the sampling technique using confirmatory factors analysis. There are four main factors finding in this research as the factors location decision making which are Proximity to Consumer and Environment¸ Quality Of the Location, Development, Accessibility. The recommendation, company should build a good relationship with customers, understand the type of the settlement, the location with complete infrastructure, understand the market opportunity, the cleanliness of the place, the location that can promote the business, proximity to the highway, the layout, and the availability of fast access and the traffic.Keywords: location, decision making, analysis factors, SME’s